ملامح المصطلح السيميائي في التراث العربي - Nadira Benzaid (UIN Fatmawati Sukarno Bengkulu, 2020)
Language undoubtedly its a means of communication among the individuals of society. Arabic constitutes a basic case in the attempt grasp its essences and variety in the frame of what is known and linguistic and non-linguistic signs. It occupies a big space in the attention of many Arab studies contemporarily and in the past. This is because it contains a lot of vocabularies, symbols, sounds and signs if need emerged to try to understand it. They are commonly referred to as linguistic and non-linguistic signs. However, their interest did not lead them to establishing theoretical rules and basics contrary to the westerners who established them as well as the terms under the name of semiology which han many fruits thanks to profound studies with certain outsets according to different bases. Hence the following problem can be set forth: What is the semiology in terms of linguistic and terminological concept? What is the subject of semiology as a humanistic field?Where are the features of semiological thinking in Arabic heritage?